Reading and study skills - Langan, John, 1942- (McGraw-Hill, 2002)
Motivational Skills; Study Skills; A Brief Guide to Important Word Skills; Reading Comprehension Skills...
Includes bibliographical references and index.
Keywords: Study skills; Reading (Higher education) -- United States